Digital literacy for the labour market: inclusive training in higher education - Barbas, Maria Potes (2020)
Understanding the term “inclusion” is a challenge today. Contemporary society assumes a diversity of definitions in order to clarify the various aspects that constitute this domain. This, in an attempt to correspond to the globality that the concept of inclusion entails. However, applying “inclusion” in a real context and effectively, specifically, social and digital inclusion for students with intellectual difficulties, is a real challenge, because in addition to forcing a paradigm shift in the context where the experience is inserted, it adds a sense of responsibility and adaptability in the institutions and human resources that perform their profession in them. In this case, it is about the creation of a unique model in Portugal of training in Higher Education, to train students with intellectual difficulties who want to continue their studies, improve their social, professional and digital skills and, above all, enhance a set of skills, attitudes and behaviours essential for their social and labour inclusion in the labour market. It is further added that this model is only possible with the addition of formal and academic education to the nonformal and informal education component of each student. This means that it is necessary to ensure that this training model is fully adapted to the social, pedagogical and emotional needs of each student, and it is essential to situate and understand the importance of two agents involved in this process: (i) families, who are the starting point for the motivation of this target audience and (ii) volunteers, who are from stakeholders, technicians to trainers and other students.